Controlled Hemorrhage Sensitizes Angiotensin II-Elicited Hypertension through Activation of the Brain Renin-Angiotensin System Independently of Endoplasmic Reticulum Stress. (13th January 2022) - Wu, Guo-Biao; Du, Hui-Bo; Zhai, Jia-Yi; Sun, Si; Cui, Jun-Ling; Zhang, Yang; Zhao, Zhen-Ao; Wu, Jian-Liang; Johnson, Alan Kim; Xue, Baojian; Zhao, Zi-Gang; Zhang, Geng-Shen
Abstract : Hemorrhagic shock is associated with activation of renin-angiotensin system (RAS) and endoplasmic reticulum stress (ERS). Previous studies demonstrated that central RAS activation produced by various challenges sensitizes angiotensin (Ang) II-elicited hypertension and that ERS contributes to the development of neurogenic hypertension. The present study investigated whether controlled hemorrhage could sensitize Ang II-elicited hypertension and whether the brain RAS and ERS mediate this sensitization. Results showed that hemorrhaged (HEM) rats had a significantly enhanced hypertensive response to a slow-pressor infusion of Ang II when compared to sham HEM rats. Treatment with either angiotensin-converting enzyme (ACE) 1 inhibitor, captopril, or ACE2 activator, diminazene, abolished the HEM-induced sensitization of hypertension. Treatment with the ERS agonist, tunicamycin, in sham HEM rats also sensitized Ang II-elicited hypertension. However, blockade of ERS with 4-phenylbutyric acid in HEM rats did not alter HEM-elicited sensitization of hypertension. Either HEM or ERS activation produced a greater reduction in BP after ganglionic blockade, upregulated mRNA and protein expression of ACE1 in the hypothalamic paraventricular nucleus (PVN), and elevated plasma levels of Ang II but reduced mRNA expression of the Ang-(1-7) receptor, Mas-R, and did not alter plasma levels of Ang-(1-7). Treatment with captopril or diminazene, but not phenylbutyric acid, reversed these changes. No treatments had effects on PVN protein expression of the ERS marker glucose-regulated protein 78. The results indicate that controlled hemorrhage sensitizes Ang II-elicited hypertension by augmenting RAS prohypertensive actions and reducing RAS antihypertensive effects in the brain, which is independent of ERS mechanism.